(untitled) (South East Asia Journal of Public Health, 2017)
Bangladesh, a developing country, has one of the highest rates of age-standardized mortality due to non-communicable diseases (NCDs). The prevalence of NCDs is steadily increasing within all population groups, including indigenous communities in Bangladesh. Indigenous people, non-dominant communities of society, are individuals having distinctive social, economic or political systems, and preserving own languages, cultures and beliefs. Contemporary research proposes that negative health behaviors, especially tobacco use, unhealthy diets, physical inactivity, and alcohol consumption are becoming escalating problems in Bangladesh. Indigenous communities with low health literacy are less receptive to health information and are unlikely to embrace positive health behaviors. Three major barriers to change health behaviors toward preventing NCDs among indigenous people in Bangladesh are: unawareness of the severity and/or importance of NCDs; absence of health literacy or knowledge on NCDs; and lack of advocacy for health intervention programs for indigenous patients suffering from NCDs. Intertwined within socio-economic delusions and discrepancies, indigenous people miss out on health care to prevent NCDs. Mass media campaigns have both an extensive coverage and an awareness-constructing potential to educate and influence intended audiences attitudes on changing health related behaviors. Bangladesh can change health behaviors within indigenous communities by adopting some effective strategies, including using multifaceted mass media to intensify coverage of the health campaigns, underpinning stereotyping health beliefs and conveying unidentified details about NCDs, and developing risk-reduction strategies for indigenous patients suffering from NCDs. Multi-stakeholder and intergovernmental mechanisms and mass media campaigns can be effective options for changing health behaviors of indigenous people in Bangladesh. South East Asia Journal of Public Health Vol.6(2) 2016: 17-22